2017
DOI: 10.3389/fpls.2017.00955
|View full text |Cite
|
Sign up to set email alerts
|

Generation, Annotation, and Analysis of a Large-Scale Expressed Sequence Tag Library from Arabidopsis pumila to Explore Salt-Responsive Genes

Abstract: Arabidopsis pumila is an ephemeral plant, and a close relative of the model plant Arabidopsis thaliana, but it possesses higher photosynthetic efficiency, higher propagation rate, and higher salinity tolerance compared to those A. thaliana, thus providing a candidate plant system for gene mining for environmental adaption and salt tolerance. However, A. pumila is an under-explored resource for understanding the genetic mechanisms underlying abiotic stress adaptation. To improve our understanding of the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 58 publications
(95 reference statements)
2
25
0
Order By: Relevance
“…Proline plays a crucial role in oxidative and osmotic responses in higher plants, and proline accumulation is a well-known measure adopted for alleviation of salt stress. We found that genes involved in arginine and proline metabolism were induced under stress, such as P5CS1 (Additional file 11 : Figure S6), which was consistent with our previous report [ 14 ]. Arginine and proline metabolism is one of the central pathways for the biosynthesis of the amino acids arginine and proline.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Proline plays a crucial role in oxidative and osmotic responses in higher plants, and proline accumulation is a well-known measure adopted for alleviation of salt stress. We found that genes involved in arginine and proline metabolism were induced under stress, such as P5CS1 (Additional file 11 : Figure S6), which was consistent with our previous report [ 14 ]. Arginine and proline metabolism is one of the central pathways for the biosynthesis of the amino acids arginine and proline.…”
Section: Discussionsupporting
confidence: 91%
“…In plants, many transcription factors have been identified to confer salt tolerance using transcriptomic approaches, including AP2-EREBP, bHLH, bZIP, C2H2, NAC and WRKY [ 14 , 56 58 ]. In this study, 480 TFs were differentially regulated under salt stress, suggesting that TFs play important roles in modulating the acclimation response of A. pumila to salt stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations